Penggunaan Metode Triangle dan Concentration Count dalam Penelitian Sebaran dan Populasi Gibbon (Hylobatidae) - Dones Rinaldi (Department of Forest Resources Conservation and Ecotourism - IPB University, 1992)
Stud eso n wildlife in the nature need methodolog cala pproaches which can produce precise and accurate data. In accordance with the increasing number of scicnt stws ho are Interested In study ngw ildlife in natire, many methods have been developed. This paper discusses the Triangle and Concentration Count methods whlch are appropriate for theobservatton of the wildlife distribution and populatione, specially for the wildlife species which frequently produce sound as a tool of communlcatlon or a spaccngllerr torial mechan sm. There are two ways in using those methods 1.e. parallcl and serlcs. Selection of whlch way to hc useddepends on the size of the arca, availability of time and the numl eorf observers.T h ms ethod has been applied in the study of arhorcal prrmates such as Siamang (tfylobarcs. iidac hrtRAFFLES). in Way Kamhas Natlonal Park. lampung (1')X-l). Mucllcr'a g l,hon( I-I. nt rcllcrM AKTIY) InRukit Soeharto Protection 1:orest (1987) and Ilarli-handcd gil l?oni'Lngkn('1 1, agilis I-'. CUVIIJR) In I'as rMayang. Jamhi (1990).